A magnetic resonance imaging‐based classification system for indication of trans‐sphenoidal hypophysectomy in canine pituitary‐dependent hypercortisolism. (21st April 2016) - Sato, A.; Teshima, T.; Ishino, H.; Harada, Y.; Yogo, T.; Kanno, N.; Hasegawa, D.; Hara, Y.
Abstract : Objectives: The objectives of this study were to establish a magnetic resonance imaging‐based classification system for canine hyperadrenocorticism according to pituitary gland extension, determine indications for trans‐sphenoidal hypophysectomy, and clarify the prognosis for each disease grade. Methods: A 5‐point classification system (Grades 1 to 5) was developed based on tumour extension in dorsal and cranio–caudal directions. Cases were then classified as Type A: no arterial circle of Willis or cavernous sinus involvement and Type B: cases in which these blood vessels were involved. Results: Medical records and magnetic resonance imaging data of 37 cases with hyperadrenocorticism were reviewed. Thirty‐three cases underwent surgery; 4 Grade 5 cases did not have appropriate indications for surgery, and other therapies were used. Complete resection was achieved for 3, 3, 22 and 1 Grade 1A, 2A, 3A and 3B cases, respectively. Resection was incomplete in 1, 1 and 2 Grade 3A, 3B and 4B cases, respectively. Remission was achieved in 29 cases. Recurrence occurred in 4 cases, all of which were classified as Grade 3. Clinical Significance: Dogs with Type A, Grade 1 to 3 hyperadrenocorticism had a good prognosis following trans‐sphenoidal hypophysectomy. Grade 3B, 4 and 5 cases may not be suitable for this surgery.